Pengaruh Culture Values Terhadap Organizational Citizenship Behavior Perawat RSIA Khadijah Di Kota Makassar - Nurfitriani Nurfitriani (Journal Innovation In Education, 2023)
OCB is an employee's willingness to take on roles that exceed their main role in an organization, so it is called extra-role behavior. This research aims to analyze the influence of cultural values ​​on the organizational citizenship behavior of Russian nurses in Makassar City. The type of research carried out was quantitative research using an observational study with a cross sectional study design. Data collection is in the form of a questionnaire. The sample in this study were nurses at RSIA Khadijah, Makassar City, totaling 177 respondents. The results of the research show that there is an influence of culture values ​​on the OCB of RSIA Khadijah Makassar City nurses. Culture values ​​are the variable that has the most influence on the OCB of RSIA Khadijah Makassar City nurses. It is recommended that hospital management need to pay attention to culture values ​​by utilizing language and tradition aspects, which have been done to emphasize new values ​​that employees want to develop.